Fractalkine and CX(3)CR1 regulate hippocampal neurogenesis in adult and aged rats - Bachstetter, Adam D. (2009)
Microglia have neuroprotective capacities, yet chronic activation can promote neurotoxic inflammation. Neuronal fractalkine (FKN), acting on CX(3)CR1, has been shown to suppress excessive microglia activation. We found that disruption in FKN/ CX(3)CR1 signaling in young adult rodents decreased survival and proliferation of neural progenitor cells through IL-1β. Aged rats were found to have decreased levels of hippocampal FKN protein; moreover, interruption of CX(3)CR1 function in these animals did not affect neurogenesis. The age-related loss of FKN could be restored by exogenous FKN reversing the age-related decrease in hippocampal neurogenesis. There were no measureable changes in young animals by the addition of exogenous FKN. The results suggest that FKN/ CX(3)CR1 signaling has a regulatory role in modulating hippocampal neurogenesis via mechanisms that involve indirect modification of the niche environment. As elevated neuroinflammation is associated with many age-related neurodegenerative diseases, enhancing FKN/ CX(3)CR1 interactions could provide an alternative therapeutic approach to slow age-related neurodegeneration.